Etıopathogenesis of Osteoarthritis - Kamanlı, Ayhan; Tuncer, Safiye (Fırat University, 2001)
Osteoarthritis is the most common musculoskelatal problem in the people over age 50. It is characterized by focal degeneration of joint cartilage and new bone formation at the base of the cartilage lesion and at the joint margins. It has been widely suggested that ostheoarthritis is a process, rather than a disease. In this article novel findings and current advanced about pathogenesis of osteoarthritis were reviewed.

Osteoartrit (OA) 50 yaşın üzerindeki insanlarda oldukça yaygın olarak görülen kas-iskelet sistemi problemidir. Karakteristikleri eklem kıkırdağında fokal dejenerasyon, kıkırdak lezyonu zemininde ve eklemin kenarlarında yeni kemik oluşumudur. Yaygı düşünce OA'nın bir hastalıktan çok bir süreç olduğu şeklindedir. Bu yazıda osteoartritin etyopatogenezi ile ilgili bazı yeni ilginç çalışmalar gözden geçirilmiştir.
OSTEOARTRİT ETYOPATOGENEZİ